Chemokine gene expression during allograft rejection: comparison of two quantitative PCR techniques. - Carvalho-Gaspar, M; Billing, J; Spriewald, B; Wood, K (2005)
The ability to analyse expression of genes rapidly in small samples of tissue is essential for the clinical assessment of many conditions, including the onset of rejection after transplantation. Chemokines have been shown to play a critical role in leukocyte recruitment to transplanted organs and in leukocyte localisation within tissues and antagonism of certain chemokines or chemokine receptors, identified as being up-regulated during allograft rejection, it has been shown to delay leukocyte infiltration into the graft and to prolong graft survival. The analysis of chemokine and chemokine receptor expression in allografts after transplantation may therefore be a useful early indicator of the onset of rejection. RT-PCR techniques are the most sensitive for the detection of low abundance mRNA when the amount of tissue sample is limited. Here we compared competitive-quantitative RT-PCR (CQ-PCR) with real-time PCR for the sequential quantification of chemokine transcripts after transplantation of a fully MHC mismatched mouse cardiac allograft. Although CQ-PCR was found to be an accurate and sensitive technique, real-time PCR was more sensitive and reproducible. Despite the reproducibility, differences in sensitivity between the two techniques were high. Real-time PCR avoids hazardous post-PCR manipulations thereby decreasing the potential risk of sample contamination, and offers the advantage that several genes can be analysed from small tissue samples in a shorter period of time, a key parameter for graft biopsy samples. Real-time PCR was therefore used to extend the analysis of intragraft mRNA chemokine expression levels. Expression of CXCL5 and CCL2 was found to be independent of T cell infiltration while intragraft expression of CCL3, CCL4, CCL5, CXCL9, CXCL10, XCL1 and CCL1 was clearly T cell dependent and increased significantly with time after transplantation. Overall, real-time PCR analysis showed that chemokine gene expression during rejection is clearly distinct from that in non-rejecting syngeneic grafts and is altered by the onset of infiltration of alloantigen-reactive T cells into the graft.